2016
DOI: 10.1007/s40801-016-0094-1
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Drug Use and Serum Sodium Concentrations in Older Hospitalized Patients: A Latent Class Analysis Approach

Abstract: BackgroundSeveral drugs may lower serum sodium concentrations (NaC) in older patients. However, distinguishing their individual effects is particularly difficult in this population because of the high prevalence of polypharmacy and disease states that are per se associated with hyponatremia.ObjectivesOur objective was to identify specific patterns of medication use in older hospitalized patients and determine whether these patterns were associated with serum NaC.MethodsWe collected clinical and demographic dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…27 , 33 Woodman et al assessed 14 separate drug classes and identified 3 medication patterns with serum sodium concentrations in older hospitalized patients. 34 To our knowledge, this is the first analysis that employees LCA to assess medication patterns in a cohort of heavy smokers at high risk for COPD. Furthermore, this approach of including a medication use pattern variable in an LCA model could be an innovative method adjusting the clustering of various comorbidities because medication use is a good indication of a patient’s overall clinical picture.…”
Section: Discussionmentioning
confidence: 95%
“…27 , 33 Woodman et al assessed 14 separate drug classes and identified 3 medication patterns with serum sodium concentrations in older hospitalized patients. 34 To our knowledge, this is the first analysis that employees LCA to assess medication patterns in a cohort of heavy smokers at high risk for COPD. Furthermore, this approach of including a medication use pattern variable in an LCA model could be an innovative method adjusting the clustering of various comorbidities because medication use is a good indication of a patient’s overall clinical picture.…”
Section: Discussionmentioning
confidence: 95%